Analisis Proses Manajemen Sumber Daya Manusia Di Rumah Sakit Khusus Bedah Hasta Husada - Wahyudi, Edy; lingiani, limgiani (Magister Manajemen Universitas Wisnuwardhana, 2024)
The Human Resources Management Process at Rumah Sakit Khusus Bedah Hasta Husada consists of Human Resources planning, personnel selection, training and development, and performance assessment. The Human Resource Management process influences the hospital services provided to patients. The aim of this research is to analyze the Human Resources management process at Rumah Sakit Khusus Bedah Hasta Husada. The research method used is a descriptive design, a qualitative approach using in-depth interview techniques. There were informants consisting of 5 (five) informants, namely the Head of Human Resources (HRD), Education and Training, Personal Administration, Development and Medical Services, as well as the Head of the Medical Services Division. The research data obtained was analyzed through thematic analysis. The results obtained are that the Human Resources management process at Rumah Sakit Khusus Bedah Hasta Husada carries out personnel planning if there are requests for needs in each part or section of the Hospital. In the planning stage, the focus will be on medical personnel because they have an essential role in providing care to patients. The selection stage consists of three stages, including the administration stage, psychology test, capability test according to each scientific discipline. Therefore, Human Resources (HR) management has a very urgent or important role in creating quality employees who have optimal performance.